Hubungan Self Efficacy dengan Kecemasan Mahasiswa dalam Menghadapi Skripsi di Tengah Pandemi Covid-19 - Fauzia, Ulfani (Happiness: Journal of Psychology and Islamic Science, 2022)
This study aims to determine the relationship between self-efficacy and student anxiety in dealing with thesis in the midst of the Covid-19 pandemic. The participants in this study were 64 final students who were working on their thesis. Sampling was done by random sampling. This study uses a quantitative approach and the research instrument uses the Self Efficacy Scale adapted from Bandura (1977) and the anxiety scale adapted from Nevid et al (2003). Before testing the correlation of the data, a normality test was carried out which was tested using the Kolmogrov Smirnov one sample test. The results of the data normality test show the sign value. 0.691 > 0.005, which means that the residual values are normally distributed. Data analysis used in the study was the Product moment correlation test technique from Karl Pearson with the help of the SPSS 16 Program. The results showed that there was a relationship between self-efficacy and student anxiety in dealing with thesis in the midst of the Covid-19 pandemic, with a sig value of 0.748 (p <0.05). From this study, the results of the relationship between the two variables were positively correlated, namely the higher the student's self-efficacy in dealing with thesis, the higher the student's anxiety.